Peningkatan Kapasitas Aparatur Kelurahan Sibatua Kecamatan Pangkajene Kabupaten Pangkep Terhadap Penggunaan Google Apps - Hilda Ashari; Burhan, Muh Iswal; Laila Sari, Dessy Ana; Elfira Makmur; Akhyar Muchtar (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
Abstract – By their competence, village officials are professionals who function to carry out government activities at the village level where in carrying out their duties they are required to run efficiently. To carry out these efficient community service activities, qualified personnel are required. In government activities in Sibatua Village, Pangkajene District, Pangkep Regency, the apparatus's ability is still lacking, so service activities related to the technological capabilities where needed, especially in the use of Google Apps including Google Drive, Google Forms, and Google Sheet.